Fracture anisotropy in texturized lithium disilicate glass-ceramics - Belli, Renan; Wendler, Michael; Cicconi, Maria Rita; de Ligny, Dominique; Petschelt, Anselm; Werbach, Katharina; Peterlik, Herwig; Lohbauer, Ulrich (Journal of Non-Crystalline Solids, 2018)
Lithium disilicate glass-ceramics show great potential in the fabrication of anisotropic structures due to their high-strength needle-form crystalline phase subjective to processing-induced alignment. Here we explore this strategy by focusing on the mechanistic aspects of fracture. Through different variations of the fracture toughness test we demonstrate the effect of bulk crystal orientation on fracture energy, toughening mechanisms, crystal size and aspect ratio. Using the anisotropic Poisson's ratio of the Li2Si2O5 crystal phase obtained by Resonant Ultrasound Spectroscopy, we apply the new geometry factor developed by Strobl et al. to provide a more accurate insight into the anisotropic crack propagation behavior in LS2 glass-ceramics. Raman spectra and X-Ray Diffraction patterns are resolved for the Li2Si2O5 phase aligned at plane parallel, anti-plane and random orientations.We show that Li2Si2O5 crystallites oriented perpendicular to the crack growth plane tended to induce large scale crack deflection unless the crack was forced into a straight path, thereby promoting crystallite fracture, increased K-Ic-values and accentuated R-curve behavior. Crystal aspect ratio and residual stresses in the glass have been identified as important influencing factors on crack growth behavior and toughening mechanisms.
Keywords: Lithium disilicate; Fracture toughness; Anisotropy; Crystal alignment